Manual de funcionamiento, mantenimiento y aplicación pedagógica de la embutidora manual (5L – H), para el laboratorio de investigación en cárnicos de la carrera de Agroindustria de la Universidad Técnica de Cotopaxi. - Caiza Toaquiza, Brayan Xavier (2022)
The Cotopaxi Technical University has an Agroindustry career, which is equipped a meat research laboratory, what it is found that the information lack is causing the equipment handling to be performed improperly, that is why with the purpose to strengthen the students practical training and contributing with a guide, it is elaborated the manual stuffer (5L-H) operation and maintenance manual, in order to avoid damages, and that it contributes to the equipment conservation. For the manual development was used the qualitative research types, participatory action research, inductive, hypothetical-deductive research methods, documentary analysis research techniques, observation and the research instrument, the technical sheet, specifying the generalities, characteristics, parts, requirements, operation mode from equipment, the maintenance different types, such as routine, preventive, corrective maintenance and staff safety measures, once, it is finished the manual, it is performed the practice carrying out each detailed aspect in the manual stuffing equipment operation, which, as a result, it has that all aspects, such as assembly, use, disassembly and cleaning make the stuffing equipment fully operational without defects, within the procedures are concluded, which the manual is supplied with each parameter, what must be made and the registration sheets, it can follow on the corresponding maintenance throughout its useful life.